FORMULASI SEDIAAN SALEP ANTIJERAWAT EKSTRAK ETANOL DAUN TEH HIJAU (Camellia sinensis (L.) (Kuntze) DENGAN KOMBINASI BASIS PEG 400 DAN PEG 4000 TERHADAP BAKTERI Propionibacterium acnes - Dewi Rahmawati; Galih Samodra (Pharma Xplore : Jurnal Sains dan Ilmu Farmasi, 2022)
Ointment is semisolid preparations used by topical. Leaf tea green contain beneficial flavonoid compounds, tannins and catechins as antibacterial. On research this extract leaf tea green made preparation ointment using a watersoluble base i.e combination of PEG 4000 and PEG 400 with comparison (2:3) on formula 1, (1:1) on formula 2 and (3:2) on formula 3. Research this aim for see nature physique preparation ointment as well as power resistor to bacteria Propionibacterium acnes. Test results nature physique from the three formulas include color, odor, shape, homogeneity, pH have good result during the storage period, while power spread and power sticky have less result good. The results of the One Way ANOVA analysis show that existence significant difference in the value of power spread and power sticky. The results of the paired test t test analysis show existence influence During storage to pH and power spread ointment. Test antibacterial conducted use method well. Antibacterial test results show the three formulas have zones of inhibition categorized strong.